IMPLEMENTASI FUZZY LOGIC CONTROL PADAAUTOMATIC SORTING SYSTEM UNTUK MEMILAH BARANG MENGGUNAKAN SENSOR KAMERA - Riky Tri Yunardi; Winarno; Pujiyanto (Politeknik Aceh, 2016)
An automatic parcel sorting is used for sorting the shaped box parcel to increase efficiency in the sorting process. In this research, the sorting machine is developed by implementing fuzzy logic controller using cameras on otomation system. Fuzzy logic is implemented to determine the size of the box based on broad sides of a package surface. Automatic sorting machine formed from conveyor belt can sort an object using DC servo motors. Cameras as vision sensor are utilized to detecting object with an accuracy of 87.5%. The experiments shownthe implementation of fuzzy logic controller in automatic parcel sorting can sort for three sizes classification of parcel with percentage of success are more than 80%.